Advanced papillary renal cell carcinoma: Epidemiology, genomic drivers, current therapies, and ongoing trials - Patrick L. Sweeney; Albert Jang; Shams K. Halat; Sumanta K. Pal; Pedro C. Barata (Cancer Treatment and Research Communications, 2022)
Papillary renal cell carcinoma (PRCC) is the most common subtype of non-clear cell renal cell carcinoma. PRCC can be subdivided into types 1 and 2 based on histology, each associated with different genetic mutations. The MET gene is commonly altered in type 1 PRCC while multiple alterations are involved in type 2 PRCC. PRCC is an aggressive cancer with a predominance in male and black patients and poor prognosis. Due to its rarity, there was a lack of convincing prospective data to guide treatment; hence, therapies were previously extrapolated from clear cell renal cell carcinoma with mixed results. More recently, some phase 2 trials focused on PRCC have been promising. Tyrosine kinase inhibitor (TKI) monotherapy is considered the standard of care, and combination strategies with TKIs and immune checkpoint inhibitors are emerging. Genetic profiling and large-scale clinical trials are needed to inform targeted treatment of PRCC.